2019
DOI: 10.3390/catal9010063
|View full text |Cite
|
Sign up to set email alerts
|

Review of Anodic Catalysts for SO2 Depolarized Electrolysis for “Green Hydrogen” Production

Abstract: In the near future, primary energy from fossil fuels should be gradually replaced with renewable and clean energy sources. To succeed in this goal, hydrogen has proven to be a very suitable energy carrier, because it can be easily produced by water electrolysis using renewable energy sources. After storage, it can be fed to a fuel cell, again producing electricity. There are many ways to improve the efficiency of this process, some of them based on the combination of the electrolytic process with other non-ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 58 publications
(113 reference statements)
1
38
0
Order By: Relevance
“…It has been shown that atmospheric SO 2 has a detrimental effect, not only on the environment but also human life [5,6]. With more countries and governments enforcing limitations on industry to reduce SO 2 emissions [5][6][7], new technologies are emerging for either the capture [8] or reutilisation of SO 2 [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that atmospheric SO 2 has a detrimental effect, not only on the environment but also human life [5,6]. With more countries and governments enforcing limitations on industry to reduce SO 2 emissions [5][6][7], new technologies are emerging for either the capture [8] or reutilisation of SO 2 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…While various other metals have been investigated [21], including Cu [22][23][24][25], Ni [26][27][28], Ag [29,30], Rh [31,32], Pd [24,[32][33][34][35][36], in addition to Pt [24,31,[37][38][39][40], which is still the best performing catalyst in terms of activity and stability [41][42][43]. However, major difficulties are still experienced in experiments, in part due to the occurrence of various co-adsorbed surface sulphur species, including elemental sulphur (S), sulphur oxide (SO) and sulphur trioxide (SO 3 ), amongst others [9].…”
Section: Introductionmentioning
confidence: 99%
“…The development of human society is largely based on energy consumption. Fossil fuels are the most used and oldest energy source, which has caused a number of detrimental impacts, such as increased CO 2 emissions, leading to environmental changes such as global warming. This fact by itself is already a “red alert” and is changing perceptions about energy use, and environmentally friendly energy sources, such as solar, wind power and photovoltaics, are emerging as alternatives of high interest .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of these products as fuels allows a closed carbon cycle, reducing new CO 2 emissions, but it does not address the high levels of this pollutant already in the air. The HER, on the other hand, could be a more interesting way to obtain solar fuels, since it is possible to generate “green hydrogen” and the HER presents the highest combustion power. The counterpart of this process is the O 2 evolution reaction (OER) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation